Circulating cell-free (cf)DNA analysis: Current technologies and applications in gynecologic cancer - Sarah H Kim; Britta Weigelt (Elsevier, 2024)
Cell-free DNA (cfDNA) analysis has several promising clinical applications in the management of cancer patients, with clinical validity established in different types of solid tumors (e.g., lung, breast, and colon cancer). Cancers harbor unique genetic alterations that can be detected in the plasma and other bodily fluids of cancer patients, constituting an alternate source of tumor-derived DNA. Technologic advances and wide-spread availability of next-generation sequencing (NGS) have made sequencing analysis of circulating tumor DNA (ctDNA) possible, employing both off-the-shelf and personalized tumor-informed panels. Tumor size, disease burden and high-grade histologic types have been shown to correlate with ctDNA levels across multiple solid cancer types. Detection of tumor-derived genetic alterations in plasma-derived cfDNA can facilitate diagnosis, guide treatment selection, and serve as a biomarker for treatment response and prognostication. Molecular residual disease (MRD) is at the forefront of cfDNA analysis, with implications in treatment de-escalation/ escalation in the neoadjuvant and adjuvant settings. The development of cfDNA analysis in early detection of cancers is under active investigation. Proof-of-principles studies in gynecologic cancers have demonstrated feasibility and potential for innovation in cancers lacking specific biomarkers, including the tracking of human papillomavirus (HPV) cfDNA in patients with cervical cancer. In this review, we outline the assays currently available for cfDNA sequencing/ ctDNA detection, the role of cfDNA analysis in clinical decision-making and the current status and potential clinical uses of cfDNA research in gynecologic cancers.